Visual discrimination impairment after experimental stroke is associated with disturbances in the polarization of the astrocytic aquaporin-4 and increased accumulation of neurotoxic proteins - Sanchez-Bezanilla, Sonia (2021)
Numerous clinical studies have documented the high incidence of cognitive impairment after stroke. However, there is only limited knowledge about the underlying mechanisms. Interestingly, there is emerging evidence suggesting that cognitive function after stroke may be affected due to reduced waste clearance and subsequent accumulation of neurotoxic proteins. To further explore this potential association, we utilised a model of experimental stroke in mice. Specifically, a photothrombotic vascular occlusion targeting motor and sensory parts of the cerebral cortex was induced in young adult mice, and changes in cognition were assessed using a touchscreen platform for pairwise visual discrimination. The results showed that the execution of the visual discrimination task was impaired in mice 10 to 14 days post-stroke compared to sham. Stroke also induced significant neuronal loss within the peri-infarct, thalamus and the CA1 sub-region of the hippocampus. Further, immunohistochemical and protein analyses of the selected brain regions revealed an increased accumulation and aggregation of both amyloid-β and α-synuclein. These alterations were associated with significant disturbances in the aquaporin-4 protein expression and polarization at the astrocytic end-feet. The results suggest a link between the increased accumulation of neurotoxic proteins and the stroke-induced cognitive impairment. Given that the neurotoxic protein accumulation appeared alongside changes in astrocytic aquaporin-4 distribution, we suggest that the function of the waste clearance pathways in the brain post-stroke may represent a therapeutic target to improve brain recovery.